2014
DOI: 10.1002/stem.1589
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Regulates Homeostasis of Pluripotency-Associated Proteins in hESCs

Abstract: The pluripotency of embryonic stem cells (ESCs) is maintained by intracellular networks of many pluripotency-associated (PA) proteins such as OCT4, SOX2, and NANOG. However, the mechanisms underlying the regulation of protein homeostasis for pluripotency remain elusive.Here, we first demonstrate that autophagy acts together with the ubiquitin-proteasome system (UPS) to modulate the levels of PA proteins in human ESCs (hESCs). Autophagy inhibition impaired the pluripotency despite increment of PA proteins in hE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 40 publications
2
31
0
1
Order By: Relevance
“…Under culture conditions permissive for the propagation of primed ESCs and where there is an abundance of nutrients, autophagy occurs at a basal level and therefore its deficiency has no detrimental effect in both mESCs and hESCs (Mizushima et al, 2001;Cho et al, 2014). However, stress conditions such as starvation act to reduce mTORC1 signalling, leading to the activation of autophagy, which is required to support ESC homeostasis via the expression of pluripotent genes (Mizushima et al, 2001).…”
Section: (Box 2)mentioning
confidence: 99%
See 1 more Smart Citation
“…Under culture conditions permissive for the propagation of primed ESCs and where there is an abundance of nutrients, autophagy occurs at a basal level and therefore its deficiency has no detrimental effect in both mESCs and hESCs (Mizushima et al, 2001;Cho et al, 2014). However, stress conditions such as starvation act to reduce mTORC1 signalling, leading to the activation of autophagy, which is required to support ESC homeostasis via the expression of pluripotent genes (Mizushima et al, 2001).…”
Section: (Box 2)mentioning
confidence: 99%
“…However, stress conditions such as starvation act to reduce mTORC1 signalling, leading to the activation of autophagy, which is required to support ESC homeostasis via the expression of pluripotent genes (Mizushima et al, 2001). Deficiency of autophagy in ESCs under such stress conditions leads to apoptosis or detrimental accumulation of pluripotency-associated proteins that compromise the pluripotent state (Mizushima et al, 2001;Cho et al, 2014). Expanding on the crucial role of mTORC1 in nutrient sensing, several amino acid pathways have been reported to be essential for the maintenance of PSC properties Carroll et al, 2016;Shiraki et al, 2014;Carey et al, 2015).…”
Section: (Box 2)mentioning
confidence: 99%
“…Given recent findings that mTOR activation can be controlled by the interplay between AKT kinase and AMPK, there is now extensive evidence validating various components of this pathway as potential molecular targets for cancer treatment. Autophagy can induce both cell survival and cell death under nutrient starvation, tumorigenesis including breast cancer,15 neurodegeneration, and other physiological and pathological processes 16,17. The conversion of LC3-I to LC3-II reflects the occurrence of autophagy 18.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has shown that SOX2-induced suppression of mTOR is necessary for induced pluripotent stem cell generation (8), and although they did not look at DEPTOR, it is plausible that DEPTOR is the intermediate in the process based on our data. Overall, the Deptor-mTOR pathway very likely modulates pluripotency by regulating protein synthesis and autophagy by post-transcriptionally balancing the pluripotency network and repressing the differentiation network (9,30).…”
Section: Discussionmentioning
confidence: 99%